Postprandial changes in glucose oxidation and insulin sensitivity in metabolic syndrome: Influence of fibroblast growth factor 21 and vitamin D status - Pathak, K.; Soares, M.; Zhao, Yun; James, A.; Sherriff, Jill; Newsholme, Philip (Emerald Group Publishing, 2017)
© 2016 Elsevier Inc.Objective Metabolic inflexibility due to insulin resistance has been reported in metabolic syndrome (MetS). Fibroblast growth factor 21 (FGF21) and vitamin D status may improve insulin sensitivity. The aim of this study was to investigate glucose-induced thermogenesis and oxidation in MetS, and to examine whether changes in FGF21 or prevailing vitamin D status modulated defined metabolic parameters. Methods Forty-eight overweight and obese older adults (14 men, 34 women; ages 51 ± 15 y) were studied. Resting metabolic rate (RMR) and respiratory quotient (RQ) were measured before and intermittently for 2 h after an oral glucose tolerance test (OGTT). The total area under the curve (TAUC) was calculated. Insulin sensitivity index (ISI) was determined as 104/(insulin × glucose) for fasting and 2 h venous blood. Fat mass (FM) and fat free mass (FFM) were measured by dual-energy x-ray absorptiometry. Participants were grouped by metabolic syndrome (MetS+ for disease presence; MetS- when no disease was present) and by median 25 hydroxyvitamin D (OHD) concentration as VD_low and VD_high. 25 OHD was also tested as a continuous variable. A parsimonious 2 × 2 analysis of variance included age, FM, FFM and MetS × sex interaction. Results Adjusted RMR was similar between groups but an interactive effect of MetS and sex was noted. Fasting RQ was significantly different between vitamin groups (VD_low: 0.835 ± 0.008 versus VD_high: 0.810 ± 0.008; P = 0.024) and fasting ISI was significantly greater in MetS- compared with MetS+ (P = 0.037). Postglucose increases in thermogenesis, RQ, and FGF21 were significant, but ISI decreased. Adjusted postprandial TAUC_RQ (VD_low: 1.71 ± 0.01; VD_high: 1.74 ± 0.001; P = 0.041) and ISI_2 h (VD_low: 35.41 ± 0.21; VD_high: 101.90 ± 0.21; P = 0.001) were significantly different. Adjusted FGF21 was similar across all comparisons before and after OGTT. Conclusions Higher vitamin D status, but not FGF21, was associated with greater postprandial glucose oxidation and improved insulin sensitivity.